Are there alternative adaptive strategies to human pro-sociality? The role of collaborative morality in the emergence of personality variation and autistic traits. (1st October 2016) - Spikins, Penny; Wright, Barry; Hodgson, Derek
ABSTRACT: Selection pressures to better understand others' thoughts and feelings are seen as a primary driving force in human cognitive evolution. Yet might the evolution of social cognition be more complex than we assume, with more than one strategy towards social understanding and developing a positive pro-social reputation? Here we argue that social buffering of vulnerabilities through the emergence of collaborative morality will have opened new niches for adaptive cognitive strategies and widened personality variation. Such strategies include those that that do not depend on astute social perception or abilities to think recursively about others' thoughts and feelings. We particularly consider how a perceptual style based on logic and detail, bringing certain enhanced technical and social abilities which compensate for deficits in complex social understanding could be advantageous at low levels in certain ecological and cultural contexts. 'Traits of autism' may have promoted innovation in archaeological material culture during the late Palaeolithic in the context of the mutual interdependence of different social strategies, which in turn contributed to the rise of innovation and large scale social networks.